Creative Development of 4th Graders by Using a Set of Learning Management Activities Based on the STEAM Concept - Bun-aran, Chawarit; Prasertsang, Parichart (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This research aimed to develop the creativity of 4th-grade students by using a set of learning activities based on the STEAM concept. The target group in this research is 4th grade students in elementary school in Thailand, during the second semester of the academic year 2023- 2024. There were 13 respondents in this research. The tools used in this research were a set of learning activities based on the STEAM concept, Academic Career Grade 4 Student Performance Assessment Form, and Student Interview Form. The research methodology was classroom action research. Data were analyzed using mean, standard deviation, and percentage, which were researched in two operating cycles. The results showed that in Operation Cycle 1, 9 students passed the assessment criteria of 70 percent out of a total of 13 students, representing 69.24 percent of the total students. In Operation Cycle 2, 13 students passed the assessment criteria of 70 percent, representing 100 percent of all students.